Association of behavior pattern with overweight and obesity in South Korean adults-A multi correspondence analysis (KNHANES-2018-2020). - Do Hee Kim; Vasuki Rajaguru; Bomgyeol Kim; Suk-Yong Jang; Jaeyong Shin; Sang Gyu Lee; Tae Hyun Kim (PLOS Global Public Health, 2023)
The objective was to determine the association between health-related behaviour with overweight and obesity in South Korean adults by using the Korean National Health and Nutritional Examination Survey (KNHANES) 2018-2020. The study participants were 16,784 aged ≥ 20years. The variables were socio-demographic, lifestyle, food habits and metabolic conditions. The logistic regression analysis performed to find the association by the odds ratio (OR, 95% CI). MCA performed to identify risk factors were computed for overweight and obesity. Overweight and obesity were significantly associated with health behaviour, high income (OR = 1.26; 95% CI: 1.15-1.39), smoking(OR = 1.29; 95% CI: 1.08-1.53), low physical activity(OR = 3.23; 95% CI: 1.79-4.69), diabetes(OR = 2.70; 95% CI: 1.62-4.50), high cholesterol and low HDL(OR = 3.98; 95%CI:2.65-5.97). The high discriminant variables of MCA were aged over 60years, lower education, high income, diabetes, lack of physical activity, and high cholesterol. The findings confirm that the OR of obesity and overweight was likely associated with health behaviour patterns. Besides, it indicates the MCA would be very effective to identify the population-based data context than individual data and it may suggest that more research on association between health behaviours and obesity prevention interventions should be developed for each age group for better health outcomes.